2017
DOI: 10.1071/mf16385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high pCO2 on early life development of pelagic spawning marine fish

Abstract: The present study investigated the effect of elevated pCO2 on the development of early stages of the pelagic spawning marine fish Solea senegalensis, Diplodus sargus and Argyrosomus regius. Eggs and larvae were reared under control (pH 8.0, ~570μatm) and two elevated pCO2 conditions (pH 7.8, ~1100μatm; pH 7.6, ~1900μatm) until mouth opening (3 days post-hatching). Egg size did not change with exposure to elevated pCO2, but hatching rate was significantly reduced under high pCO2 for all three species. Survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Hatching often presents a critical bottleneck in the life history of marine fish (Köster et al 2003;Houde 2008;Dahlke et al 2020a). Reduced hatching in response to high ρCO 2 has been observed in some marine fish, including Senegalese Sole Solea senegalensis (Pigmental et al 2014;Faria et al 2017), White Seabream Diplodus sargus, and Meagre Argyrosomus regius, as well as crustaceans, including Florida stone crab Menippe mercenaria (Gravinese 2018), Antarctic krill Euphausia superba (Kawaguchi et al 2013), and the copepod Calanus finmarchicus (Mayor et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Hatching often presents a critical bottleneck in the life history of marine fish (Köster et al 2003;Houde 2008;Dahlke et al 2020a). Reduced hatching in response to high ρCO 2 has been observed in some marine fish, including Senegalese Sole Solea senegalensis (Pigmental et al 2014;Faria et al 2017), White Seabream Diplodus sargus, and Meagre Argyrosomus regius, as well as crustaceans, including Florida stone crab Menippe mercenaria (Gravinese 2018), Antarctic krill Euphausia superba (Kawaguchi et al 2013), and the copepod Calanus finmarchicus (Mayor et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Otoliths are composed of aragonite [33,34] and it was initially thought that otolith calcification might be impaired in acidified conditions due to reduced carbonate saturation in low pH seawater [35]. However, a consistent finding in fish ocean acidification research is that otoliths are often larger in larval fishes exposed to elevated CO 2 conditions [33,[36][37][38][39][40]. For example, Bignami et al [36] showed that the sagittal otoliths of larval cobia (Rachycentron canadum) had 49% greater volume and 58% greater mass in fish reared under increased CO 2 saturation (2100) µatm compared to control fish.…”
Section: Introductionmentioning
confidence: 99%
“…Originally, it was predicted that CO2-induced ocean acidification (OA) would impair otolith biomineralization because the associated decreases in seawater pH and [CO3 2-] hamper CaCO3 precipitation [9]. However, subsequent studies reported that fish exposed to OA developed enlarged otoliths [10][11][12][13][14][15][16]. These findings led to a broader awareness otolith biomineralization is strongly linked to endolymph and blood chemistries, and to the hypothesis that biological regulation of endolymph pH could lead to increased [CO3 2-] resulting in otolith overgrowth [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, splitnose rockfish ( Sebastes diploproa) were exposed to ~1,600 μatm CO 2 (pH ~7.5), a condition readily experienced in their natural habitat [31,32] and predicted for the surface ocean by the year 2300 [33]. The OA exposure spanned three days, a duration previously documented to result in otolith overgrowth [16]. Blood acid-base chemistry was measured after taken samples using a benzocaine-based anesthetic protocol that yields measurements comparable to those achieved using cannulation [20].…”
Section: Introductionmentioning
confidence: 99%